The Battle for Rome - Jackson, W. G. F. (New York Bonanza Books)
Describes the battle for Rome and the capture of the same during World War II.
Include Maps, Illustrations, Appendices, Bibliography and Index.
Keywords: World War (1939-1945) -- Italy--Rome -- Italy -- Military campaigns